Managing university crises through psychological distance and information strategies - Xiaoyu Jiang; Shougui Pang; Syafila Kamarudin; Shuhui Li; Kai Wang (Scientific Reports)
Abstract Higher education institutions experiencing organizational misconduct frequently need to communicate with the public to reduce reputation damage and diminishing supportive intentions. Whether such information should be abstract or concrete is still being debated. This study investigates the effectiveness of organizational information strategy through an online factorial experiment, grounded in the principles of situational crisis communication theory and construal-level theory. The findings indicate that concretely developed information strategies are more effective when the organization is viewed as psychologically close to (rather than distant from) the public. Similarly, abstractly articulated information strategies work better when the organization is viewed as psychologically near. Finally, research reveals that information strategy exerts a greater influence on organizational reputation and supportive intention than temporal and spatial distance. By including information construal levels and psychological distance in crisis response strategies, this study provides helpful guidance for universities to manage crises efficiently.